ADEQUAÇÃO DE DIETAS PARA CRIAÇÃO DE ADULTOS DE CHRYSOPERLA EXTERNA (HAGEN) (NEUROPTERA: CHRYSOPIDAE) - Pessoa, L.g.a.; Freitas, S. De [UNESP]; Loureiro, E. De S. (Instituto Biológico, 2021)
This work was aimed to evaluate the response of adults of Chrysoperla externa fed different diets. Adults from F2 offspring were individualized in PVC cages and received food, formed by yeast + honey (standard diet), sugarcane yeast + honey and soy extract + honey, at 1:1. The bioassays were conducted at 25 ± 2º C, 60 ± 10% of RH and 12-hour photophase. Over a period of 60 days, evaluations were made of the period of pre-oviposition, daily and total oviposition, the viability of the eggs and the exploitation index (EI). It was verified that the diet containing sugarcane yeast + honey was similar to the standard diet. It was also verified that no diet interfered with the pre-oviposition and egg viability. Only for the insects fed soy extract + honey was there a significant reduction in the values of the daily and total oviposition and the exploitation index. Under the tested conditions and proportions, the diet formed by sugarcane yeast + honey was suitable for the rearing of C. externa adults, and can be used to replace the diet formed by yeast + honey.

Objetivou-se avaliar a resposta de adultos de Chrysoperla externa alimentados com diferentes dietas. Adultos da geração F2 foram individualizados em gaiolas de PVC e alimentados com lêvedo de cerveja+mel (dieta padrão), lêvedo de cana + mel e extrato de soja + mel (1:1). Os bioensaios foram conduzidos a 25 ? 2º C, 60 ? 10% de UR e fotofase de 12 horas. Avaliou-se, durante 60 dias, o período de pré-oviposição, oviposição diária e total, viabilidade dos ovos e índice de aproveitamento (IA). Verificou-se que a dieta composta por lêvedo de cana + mel foi semelhante à dieta padrão. Também se verificou que as dietas não interferiram sobre o período de pré-oviposição e a viabilidade dos ovos. Apenas para os insetos alimentados com extrato de soja + mel observou-se redução significativa na oviposição diária, oviposição total e índice de aproveitamento. A dieta composta por lêvedo de cana + mel foi adequada para criação de adultos de C. externa podendo ser utilizada em substituição à dieta composta por lêvedo de cerveja + mel.
SUITABILITY OF DIETS FOR REARING OF ADULTS OF CHRYSOPERLA EXTERNA (HAGEN) (NEUROPTERA: CHRYSOPIDAE)
Keywords: Biological control; green lacewing; mass rearing; Controle biológico; crisopídeo; criação massal